Euro-English and Croatian national identity - Stanojević, Mateusz-Milan (2010)
OBJECTIVES: The objective of the research is to establish the impact of globalisation and the possible emergence of a Euro-English on the attitude of Croats towards their foreign accent. As one's foreign accent gives away one's national identity, the extent to which one consciously strives to approach native-like pronunciation or preserve and display features of one's national identity varies considerably and depends on a number of factors. In particular, we look at how parameters like sex ; proficiency in English ; the sociolinguistic status of the subject's regional dialect of Croatian ; regional pride ; and inclination towards perfectionism influence their motivation to work on their English pronunciation. We also study the way in which the subjects' feeling of regional pride correlates with the inclination to display their Croatian accent in English pronunciation. In this context we aim at reaching some conclusions about the importance that Croatian learners of English attach to the work on the improvement of their accent. Finally, the research also aimes at establishing the subjects' preferences concerning the native vs. non-native status of their English teachers.The research is set within the theoretical framework of the sociolinguistic debate between the so-called 'deficit' vs. 'liberational' approach to chosing the model for teaching English as a second language. Though applied to English as a foreign, rather than a second language, the present research is aimed at challenging the present way of teaching English in Croatia, which has traditionally been based on two major 'metropolitan' varieties of English as desirable models in English teaching, largely ignoring and often stigmatising any regionally or nationally recognisable features of English pronunciation. METHODS: The research is carried out in the form of a questionnaire including 20 questions. It is anonymous, takes 10 minutes to complete and is done on a voluntary basis during regular university classes. The subjects include various profiles of students. The subjects' responses are analysed by means of the SPSS software. RESULTS: The most striking result is the tendency among subjects to consider the work on the improvement of one's English pronunciation as a waste of time. It is also interesting that the subjects tend to prefer non-native teachers of English pronunciation, which suggests that they do not mind learning to pronounce English with their national accent. The majority of subjects give extreme responses in either direction in connection with their readiness to display their regional accent of Croatian. It turns out that the attitude towards one's own foreign accent does not depend on whether the collocutor is a native speaker of English or not. These results are discussed with reference to current sociophonetic and motivational research. CONCLUSIONS: The conclusions based on these results have implications for the future of teaching English in the contemporary globalisation context: some formerly stigmatised regional and national features of English pronunciation may become fully acceptable.